2010
DOI: 10.1111/j.1600-0633.2010.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of burbot (Lota lota L.) in Lake Erie: an empirical modelling approach

Abstract: World-wide, many burbot Lota lota (L.) populations have been extirpated or are otherwise in need of conservation measures. By contrast, burbot made a dramatic recovery in Lake Erie during 1993-2001 but declined during 2002-2007, due in part to a sharp decrease in recruitment. We used Akaike's Information Criterion to evaluate 129 linear regression models that included all combinations of one to seven ecological indices as predictors of burbot recruitment. Two models were substantially supported by the data: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Cohort strength does not appear to be closely related to spawner abundance in Columbia Lake, as has been observed for the West Arm of Kootenay Lake (Ahrens and Korman 2002) and Lake Erie (Stapanian et al 2010b). In this study, the lowest tributary spawner count was in 1999, yet the 1999 cohort appeared to be the strongest since 1993 based on 2001 tributary returns.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Cohort strength does not appear to be closely related to spawner abundance in Columbia Lake, as has been observed for the West Arm of Kootenay Lake (Ahrens and Korman 2002) and Lake Erie (Stapanian et al 2010b). In this study, the lowest tributary spawner count was in 1999, yet the 1999 cohort appeared to be the strongest since 1993 based on 2001 tributary returns.…”
Section: Discussionsupporting
confidence: 46%
“…Therefore, the effect of tributary temperature on egg survival does not appear to explain the greater juvenile recruitment success of the 1997 cohort relative to that of the 1996 cohort. In Lake Erie, Stapanian et al (2010b) found an association between Burbot recruitment and an index of the number of days with optimal water temperature for spawning and development, if combined in a model with Yellow Perch Perca flavescens abundance. However, when considered alone, the temperature index was not supported as a predictor of recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recovery of Burbot populations in the lower Great Lakes was short-lived, as declines were evident by the 2000s. These have been attributed to a mix of factors, including reduced recruitment, increased Sea Lamprey depredation, and predation on larval fish (Stapanian et al 2008(Stapanian et al , 2010, though food web changes driven by the invasion of dreissenid mussels in these Great Lakes have yet to be implicated.…”
Section: Discussionmentioning
confidence: 99%
“…This species is vulnerable to many environmental changes, in particular, warming water temperatures and pollution (Stapanian, Paragamian, et al, 2010; Stapanian et al, 2010). The burbot in marginal habitats may serve as an early indicator of the impacts of climate change on cold‐water fish species (Stapanian, Paragamian, et al, 2010; Stapanian, Witzel, et al, 2010). However, burbot stocks have severely declined in number and distribution during the past century.…”
Section: Introductionmentioning
confidence: 99%
“…Many populations are threatened, have been extirpated, or are otherwise in need of conservation measures (Maitland & Lyle, 1990). For example, burbot has been extirpated from the United Kingdom, and its populations in Finland have declined or have been destroyed entirely in 16% of the lakes (Stapanian, Paragamian, et al, 2010; Stapanian, Witzel, et al, 2010; Tammi et al, 1999). A series of threats, including pollution, habitat fragmentation, exploitation, and invasive species, has caused the decline or extirpation of many burbot populations (Stapanian, Paragamian, et al, 2010; Stapanian, Witzel, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%